2012
DOI: 10.1001/jama.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Reexcision Following Breast Conservation Surgery

Abstract: Context Health care reform calls for increasing physician accountability and transparency of outcomes. Partial mastectomy is the most commonly performed procedure for invasive breast cancer and often requires reexcision. Variability in reexcision might be reflective of the quality of care.Objective To assess hospital and surgeon-specific variation in reexcision rates following partial mastectomy. Design, Setting, and Patients An observational study of breast surgery performed between 2003 and 2008 intended to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
336
6
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(361 citation statements)
references
References 31 publications
14
336
6
5
Order By: Relevance
“…Prostate cancer mortality and incidence data were obtained from a merged data set from the National Cancer Institute's Surveillance, Epidemiology and End Results program, National Program for Cancer Registries and United States Center for Disease Control and Prevention's National Vital Statistics System. 12 …”
Section: Data Sourcesmentioning
confidence: 99%
“…Prostate cancer mortality and incidence data were obtained from a merged data set from the National Cancer Institute's Surveillance, Epidemiology and End Results program, National Program for Cancer Registries and United States Center for Disease Control and Prevention's National Vital Statistics System. 12 …”
Section: Data Sourcesmentioning
confidence: 99%
“…Preoperative mammography, ultrasonography, or MRI may be used by the surgeon to guide adequate resection (4)(5)(6). Despite numerous improvements in imaging and surgical technique, the need for reexcision to achieve complete tumor resection in the United States typically ranges from 20-40% (7)(8)(9)(10)(11)(12)(13)(14)(15), and has been reported as being as high as 60% (16). The importance of reexcision is underscored by numerous studies, which have shown that incomplete resection of tumor and positive margins are associated with increased locoregional recurrence compared with negative margins (12,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…There is the potential for the wire to be displaced between the time of its image guided placement and subsequent removal in the operative suite. The surgical margins are frequently positive, which then requires an additional surgical procedure to remove more breast tissue to obtain clear margins (Cody & Van Zee, 2015;McCahill et al, 2012). A recent report from the National Cancer Database including 316, 114 patients undergoing breast conserving surgery from 2004 through 2010, demonstrated roughly one-fourth of patients required a second procedure (Wilke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%